The Assessment of Service Quality of PT Interlink Tour and Travel in Bandung Using Servqual Scale and Time Study Analysis - Destiny, Tirza; Adhiutama, Akbar (Journal of Business and Management, 2014)
The current competition of tour and travel industry in Bandung is fierce, since currently there are more than one hundred tour and travel companies in Bandung. A lot of similar companies are engaged in the same field (i.e. the service products offered are similar). To survive in the long run and to be able compete, the key is simply to build customers’ trust and loyalty and to provide high quality service. This research focuses on the service quality of PT. Interlink Tour and Travel, investigating the gap between customer expectations and perceptions of the company’s service (i.e. known as SERVQUAL). In addition, this research also addresses the operation system of front line desk people who are in charge in directly serving the customer at PT. Interlink Tour and Travel.For this purpose, questionnaires have been designed based on SERVQUAL method (i.e. the gap between customer perceptions and expectations of the service) proposed by Parasuraman et al. (1985 and 1988). A total number of 101 regular customers from PT. Interlink Tour and Travel participated in this research. For the operation system of front line desk employees, observations based on Time Study analysis have been conducted. The findings show that all scores for perceptions were lower than the expectations scores, indicating that the service in PT. Interlink Tour and Travel did not meet the expectations of the customers. Although the perceptions score were lower, it was shown that 71% of total respondent were willing to experience the service again. This could mean that the service perceived is still in the zone of tolerance. The largest gap can be found in the tangible dimension, followed by the reliability dimension. Overall, it seems that the company needs to start focusing on the tangible dimension by developing marketing communication such as pamphlets or posters regularly and the reliability dimension as by giving precise service delivery. The findings from the time study observation suggest that the total time of each process is unstable. It is also revealed that compared to its competitor, the operation system in the front line desk at PT. Interlink Tour and Travel takes longer. There are several non-value added steps in the process that may lead to customers’ dissatisfaction. Based on this observation, the current service in front line desk is still lacking in the responsiveness dimension. If the lack in responsiveness continues, it may lead to an overall bad service quality and customers’ dissatisfaction or even loss of customers. Since customers generally want to feel valued, they want faster response.By using SERVQUAL, service quality can be understood in the perspective of the consumer. This method aims to determine whether the service needs to be fixed or the extent to which services need to be improved in the eyes of consumers. Time study analysis is useful to specifically understand to a certain extent the condition of service in the frontline desk, enriching our understanding of PT. Interlink Tour and Travel’s service quality. This study is particularly related to the responsiveness dimension, one of the service quality dimensions measured in SERVQUAL. Keywords: Service Quality, Customer Gaps, Travel Agency, Time Studies